E-Commerce, Fintech, dan Media Sosial: Dampaknya terhadap Pendapatan UMKM Lubuklinggau - Kesuma, Indrawati Mara (Jurnal Ilmu Akuntansi, 2025)
This study aims to determine the effect of e-commerce and fintech on increasing income through social media as a mediating variable in MSMEs in Lubuklinggau City. This type of research is quantitative. The population in this study were 7,105 MSMEs in Lubuklinggau City in the trade and culinary business sectors. The sampling technique used was nonprobability sampling and purposive sampling with a sample of 100 respondents. The variables used in this study consist of three, namely the dependent variable (Y), the independent variable (X), and the mediating variable (Z). The dependent variable in this study is income increase. There are two independent variables in this study, namely e-commerce and fintech. Meanwhile, the mediating variable in this study is social media. The analysis methods used in this study are instrument testing, classical assumption testing, model consistency testing, multiple linear regression, t-test, path analysis, and Sobel test, while data processing uses the IBM SPSS 27 program. Based on the results of this study, it shows that e-commerce and fintech have a positive and significant effect on social media, e-commerce and fintech have a positive and significant effect on increasing income, social media has a positive and significant effect on increasing income. The results of this study also show that social media can mediate the effect of e-commerce on increasing income. In addition, social media can mediate the effect of fintech on increasing income.